2021
DOI: 10.3390/toxics9020031
|View full text |Cite
|
Sign up to set email alerts
|

First Assessment of Plasticizers in Marine Coastal Litter-Feeder Fauna in the Mediterranean Sea

Abstract: Micro and nanoplastics are harmful to marine life due to their high level of fragmentation and resistance to degradation. Over the past two decades, marine coastal sediment has shown an increasing amount of microplastics being a sort of trap for debris wastes or chemicals. In such an environment some species may be successful candidates to be used as monitors of environmental and health hazards and can be considered a mirror of threats of natural habitats. Such species play a key role in the food web of littor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 36 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…With recent advancements in tools that enabled the characterization of MPs in food, water, and air, we have seen colossal data sets generating strong evidence concerning MPs nature, chemical composition, reactivity, and structures (Kik et al 2020 ; Lo Brutto et al 2021 ; Ripken et al 2021 ).…”
Section: Microplastics As a Public Health Concernmentioning
confidence: 99%
“…With recent advancements in tools that enabled the characterization of MPs in food, water, and air, we have seen colossal data sets generating strong evidence concerning MPs nature, chemical composition, reactivity, and structures (Kik et al 2020 ; Lo Brutto et al 2021 ; Ripken et al 2021 ).…”
Section: Microplastics As a Public Health Concernmentioning
confidence: 99%
“…Lo Brutto et al [24] have detected the presence of plasticizers and toxic derivatives of microplastic contamination in amphipods such as Talitrus saltator, Parhyale plumicornis, Parhyale aquilina, Speziorchestia stephenseni, and Orchestia montagui using GC-MS. The results showed that DEP and DiBP represented the most abundant compounds in the selected amphipods.…”
Section: Detection Of Mps In Marine and Freshwater Organismsmentioning
confidence: 99%
“…The ecological status of submerged sandy beaches can be assessed by analyzing the composition and abundance of benthic macrofauna as macrofauna living in the intertidal zone can be particularly vulnerable to beach activities and disturbances [37][38][39][40]. Even if the data on specific impacts influencing macrofauna are limited, the number of studies regarding the response of macrofaunal communities and populations towards physical disturbances has increased in recent decades [41][42][43][44][45][46][47][48][49]. Some of the studies are based on single indicator species, while others are focused on the overall macrofaunal community.…”
Section: Introductionmentioning
confidence: 99%